L-Cysteine Increases the Transformation Efficiency of Chinese Cabbage (Brassica rapa ssp. pekinensis) - Sivanandhan, Ganeshan; Moon, Jiae; Sung, Chaemin; Bae, Solhee; Yang, Zhi Hong; Jeong, So Young; Choi, Su Ryun; Kim, Sang-Gyu; Lim, Yong Pyo (Frontiers in Plant Science, 2021)
Successful Agrobacterium-mediated transformations of Chinese cabbage have been limited owing to the plant’s recalcitrant nature, genomic background and explant necrosis upon infection, which hinders the transfer of T-DNA region into the Chinese cabbage. Consequently, in the current experiment, a stable Agrobacterium tumefaciens-mediated transformation method for Chinese cabbage cv. Kenshin established by employing important anti-oxidants in the co-cultivation and subsequent regeneration media. Four-day-old in vitro derived cotyledon explants were infected with A. tumefaciens strain GV3101 harboring the vector pCAMIBA1303. Cotyledon explants exposed to an Agrobacterium suspension (OD600 of approximately 0.6) for 10 min and then incubated for 3 days co-cultivation in Murashige and Skoog medium containing an L-cysteine+AgNO3 combination exhibited the highest GUS expression (94%) and explant regeneration efficiency (76%). After 3 days, the cotyledon explants were subjected to three selection cycles with gradually increasing hygromycin B concentrations (10 to 12 mg/L). The incorporation and expression of hptII in T0 transformed plants were verified by polymerase chain reaction and Southern blot analyses. These transgenic plants (T0) were fertile and morphologically normal. Using the present protocol, a successful transformation efficiency of 14 % was achieved, and this protocol can be applied for genome editing purposes to improve Chinese cabbage traits.